Transcriptomic analysis reveals molecular mechanism by which Chinese olive fruit prolongs lifespan of Caenorhabditis elegans - Yuanxin Miao; Yan Xu; Jia Gao; Xu Ai; Rui Duan; Rong Li (npj Science of Food)
Abstract Chinese olive (Canarium album L.) contains various phytochemical compositions, exhibiting multiple health-promoting bioactivities. In this study, we used Caenorhabditis elegans (C. elegans) as model organisms to investigate the anti-aging functions of Chinese olive fruit extract (COFE). The results showed that COFE contained large amounts of flavonoids and polyphenols, and thus it could strengthen stress resistance, delay aging, and promote the health of C. elegans. Furthermore, COFE improved the locomotion ability of C. elegans and reduced lipofuscin deposition. COFE also prolonged the survival time of C. elegans by affecting the Insulin/IGF-1 signaling pathway, DAF-16/FOXO, and SKN-1/Nrf2 transcription factors. Transcriptome analysis indicated that COFE treatment induced differential expression of genes related to defense response, immune response, stress response, oxidoreductase activity, and intracellular oxygen homeostasis in C. elegans. The positive results provide a theoretical basis and valuable reference for developing Chinese olive into functional food to delay aging and treat aging-related diseases.